Maize Provitamin A Carotenoids, Current Resources, and Future Metabolic Engineering Challenges - Wurtzel, Eleanore T.; Cuttriss, Abby; Vallabhaneni, Ratnakar (Frontiers in Plant Science, 2012)
Vitamin A deficiency is a serious global health problem that can be alleviated by improved nutrition. Development of cereal crops with increased provitamin A carotenoids can provide a sustainable solution to eliminating vitamin A deficiency worldwide. Maize is a model for cereals and a major staple carbohydrate source. Here, we discuss maize carotenogenesis with regard to pathway regulation, available resources, and current knowledge for improving carotenoid content and levels of provitamin A carotenoids in edible maize endosperm. This knowledge will be applied to improve the nutritional composition of related Poaceae crops. We discuss opportunities and challenges for optimizing provitamin A carotenoid biofortification of cereal food crops.